2007
DOI: 10.1093/scan/nsm005
|View full text |Cite
|
Sign up to set email alerts
|

Learning fears by observing others: the neural systems of social fear transmission

Abstract: Classical fear conditioning has been used as a model paradigm to explain fear learning across species. In this paradigm, the amygdala is known to play a critical role. However, classical fear conditioning requires first-hand experience with an aversive event, which may not be how most fears are acquired in humans. It remains to be determined whether the conditioning model can be extended to indirect forms of learning more common in humans. Here we show that fear acquired indirectly through social observation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
191
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(215 citation statements)
references
References 39 publications
19
191
1
4
Order By: Relevance
“…The mean level of average and worst pain reported by the observed participants was The present findings corroborate previous findings on vicarious fear conditioning in humans 15,16,17,42,60,72,78 and suggest that seeing others in pain has a profound influence on observers 40 . Specifically, findings indicate that other's pain can serve as a sign of threat, resulting into fearful responses towards previously neutral stimuli.…”
Section: Self-report Datasupporting
confidence: 91%
See 2 more Smart Citations
“…The mean level of average and worst pain reported by the observed participants was The present findings corroborate previous findings on vicarious fear conditioning in humans 15,16,17,42,60,72,78 and suggest that seeing others in pain has a profound influence on observers 40 . Specifically, findings indicate that other's pain can serve as a sign of threat, resulting into fearful responses towards previously neutral stimuli.…”
Section: Self-report Datasupporting
confidence: 91%
“…The heightened corrugator EMG response and fear-potentiated startle suggest the activation of a self-oriented, aversive system 26,28,39,47,48 . Supporting this idea, the amygdala, a key structure implied in fear responses, plays a critical role in the evocation of the fearpotentiated startle reflex 21,39,46,60,61 . Furthermore, research on personal pain experience has consistently shown that participants display a fear-potentiated startle when experiencing or 18 anticipating pain 25,38,41,47 , particularly when pain is perceived as highly threatening 7 Observers' distress towards pain signals in others likely serve a protective function of preparing observers for dealing with impending threat 40 .…”
Section: Self-report Datamentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, exposure to the person(s) in pain and distress is recognized as a cause of psychological distress, which can produce fear learning (Olsson et al, 2007) and elicit traits of PTSD (Eriksson et al, 2001;Figley, 1995;Munroe, 1999). Such exposure, in contrast to physical pain, recruits the brain circuits for social cognition through multimodal sensory processing.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical shocks, the most widely used UCS in adults, may not be appropriate for adolescents, yet less noxious UCSs typically provoke minimal fear in adolescents (23). To overcome these barriers, we developed a unique task that capitalizes on the intrinsic aversiveness of witnessing fear in others (24). Thus, the task uses a fearful facial expression paired with a scream as the UCS (23).…”
mentioning
confidence: 99%